Cross-Border Acquisitions and Greenfield Entry - Pehr-Johan Norbäck; Lars Persson (The Research Institute of Industrial Economics (IUI), 2002)
We investigate the interaction between cross-border acquisitions and greenfield entry in a multi-firm setting. It is shown that the net profits of the acquirer may decrease when the acquisition gives the acquirer a strong position in the product market, relative to greenfield entrants. The reason is that the price of the assets increases more than the acquirer's profit, due to strategic interaction effects in the product market. The paper also provides an explanation why MNEs entering a new market by acquisitions may make a lower profit than MNEs entering greenfield. A greenfield entrant faces the risk of not being able to successfully locate production due to the lack of knowledge of characteristics of the local market. The bidding competition between the MNEs for being successfully located in the market then drives up the acquisition price to such a level that being a successful greenfield entrant is, ex post, more profitable.
Keywords: F21; F23; L13; 330; Investment Liberalization; FDI; Mergers & Acquisitions; Auslandsinvestition; Übernahme; Investition; Theorie